2018
DOI: 10.1007/s00425-018-2884-z
|View full text |Cite
|
Sign up to set email alerts
|

The ethylene response factor SmERF6 co-regulates the transcription of SmCPS1 and SmKSL1 and is involved in tanshinone biosynthesis in Salvia miltiorrhiza hairy roots

Abstract: The SmERF6, which recognizes the GCC-box of SmCPS1 and SmKSL1 promoter in nucleus, regulates the tanshinone biosynthesis in Salvia miltiorrhiza hairy roots. Tanshinone, an important medicinal ingredient in Salvia miltiorrhiza, is best known for its use in medicine. However, the transcription factor regulation of tanshinone biosynthesis is unclear. Here, we isolated and identified a transcription factor in the ERF family of S. miltiorrhiza, SmERF6, which was screened from an S. miltiorrhiza cDNA library by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…Note that SmIPI1 has been identified as a key enzyme in the terpenoid metabolic pathway [ 55 ]; the correlation of the transcription of SmMAPK3 with that of SmIPI1 suggested that the product of the former gene may be involved in the regulation of tanshinone synthesis. The product of SmERF6 modulates the synthesis of tanshinones through its binding to a GCC box present in the promoters of both SmCPS1 and SmKSL1 [ 56 ], while SmMYB36 interacts with many MYB-related core elements (MBSI, MBSII, AAAAAAC(C/G) GTTA, CAACTG and AAAAGTTAGTTA) present in the promoters of various genes encoding enzymes involved in the synthesis of secondary metabolites [ 57 ]. Correlations were also identified for a set of eight enzyme-encoding genes ( SmCPS1 , SmCYP76AH1 , SmCYP76AH3 , SmCYP76AK1 , SmDXR , SmGGPPS1 , SmHMGR2 and SmKSL1 ) along with three genes encoding transcription factors ( SmAREB1 , SmERF115 and SmWRKY1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Note that SmIPI1 has been identified as a key enzyme in the terpenoid metabolic pathway [ 55 ]; the correlation of the transcription of SmMAPK3 with that of SmIPI1 suggested that the product of the former gene may be involved in the regulation of tanshinone synthesis. The product of SmERF6 modulates the synthesis of tanshinones through its binding to a GCC box present in the promoters of both SmCPS1 and SmKSL1 [ 56 ], while SmMYB36 interacts with many MYB-related core elements (MBSI, MBSII, AAAAAAC(C/G) GTTA, CAACTG and AAAAGTTAGTTA) present in the promoters of various genes encoding enzymes involved in the synthesis of secondary metabolites [ 57 ]. Correlations were also identified for a set of eight enzyme-encoding genes ( SmCPS1 , SmCYP76AH1 , SmCYP76AH3 , SmCYP76AK1 , SmDXR , SmGGPPS1 , SmHMGR2 and SmKSL1 ) along with three genes encoding transcription factors ( SmAREB1 , SmERF115 and SmWRKY1 ).…”
Section: Discussionmentioning
confidence: 99%
“…ERF5 is an activator of transcription and interacts with multiple proteins, such as ERF6, ERF8, and SCL13 [46,43]. ERFs belong to the AP2/EREBP transcription factor family [26], which can strongly bind a wide range of cis-regulatory elements, in the promoter of target genes [47,48]. As the final response gene in ethylene signaling pathway, basic endochitinase precursor (NP_001267891.1) changes, proving its relation to ERF [43].…”
Section: Discussionmentioning
confidence: 99%
“…The pA7 0390- SmGRAS1/2-GFP and pA7 0390 -GFP plasmids were transformed into Agrobacterium strain GV3101 . The GV3101 suspension cultures were infiltrated into leaves of 4-week-old N. benthamiana , following the previously described method (Bai et al, 2018). After 2 days of co-culture, the protoplasts were prepared as previously described (Li, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The primers for the bait vectors ( pBait-AbAi-SmKSL1-649 ) are listed in Table S1 . Aureobasidin A (AbA) suppressed the basal expression of the Y1H-pAbAi-SmKSL1-649 ( PYK649 ) yeast strain (Bai et al, 2018). pGADT7-SmGRAS1/2 was verified by interactions with PYK649 yeast strains, which recombined the SmKSL1 promoter in SD/-Leu/AbA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation